Meningkatkan Kualitas Kehidupan Masyarakat Dengan Social Entrepreneurship - Hidayah, Mila Nur; Cahyani, Rusnandari Retno (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2024)
This study employs a qualitative method with a literature review approach to examine the development of social entrepreneurship from 2014 to 2024. The main focus of the research is the role of social innovation and community empowerment in improving social and economic welfare. The findings indicate that social entrepreneurship plays a crucial role in creating sustainable solutions to social challenges, particularly in marginalized communities. Highly cited articles, such as those by Drayton (2017) and Anderson et al. (2018), emphasize the importance of social innovation as a key factor in the success of social entrepreneurship. Furthermore, the study shows that social entrepreneurship significantly contributes to local economic growth by creating jobs and increasing income. However, challenges related to business sustainability and balancing social objectives with profitability remain obstacles that need to be addressed. This research highlights the need for education, training, and institutional and policy support to strengthen the social entrepreneurship ecosystem in the future.